2021
DOI: 10.1177/08850666211030845
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Innovative System of Open and Flexible, Patient-Family-Centered, Virtual Visiting in ICU During the COVID-19 Pandemic: A Collaboration of Staff, Patients, Families, and Technology Companies

Abstract: Few challenges of the COVID-19 pandemic strike at the very core of our humanity as the inability of family to sit at the bedside of their loved ones when battling for their lives in the ICU. Virtual visiting is one tool to help deal with this challenge. When introducing virtual visiting into our ICU, we identified 5 criteria for a sustainable system that aligned with patient-family-centered care: virtual visiting needed to (1) simulate open and flexible visiting; (2) be able to accommodate differences in famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…3,62 Telehealth was used to connect with some families; however, as previously reported, it was found that there was some resistance from staff members who felt that they were too busy, the system was not user-friendly, or devices were not readily available. 57,63,64 Innovative technology such as the Virtual Intensive Care Unit which electronically connects families and patients via smart phones and has the potential to improve communication between patient, clinician, and the family is being developed 2,63,65,66 and may be more available in the future. Communication via phone and telehealth is valuable, but the trauma inherent in having a close family member critically unwell is overwhelming, making any substitute for personal contact inadequate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,62 Telehealth was used to connect with some families; however, as previously reported, it was found that there was some resistance from staff members who felt that they were too busy, the system was not user-friendly, or devices were not readily available. 57,63,64 Innovative technology such as the Virtual Intensive Care Unit which electronically connects families and patients via smart phones and has the potential to improve communication between patient, clinician, and the family is being developed 2,63,65,66 and may be more available in the future. Communication via phone and telehealth is valuable, but the trauma inherent in having a close family member critically unwell is overwhelming, making any substitute for personal contact inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…These visiting restrictions have challenged the role of the family in patient care and recovery and have had a distressing impact on many families. 2 Families normally play a pivotal role in the care of patients in the intensive care unit (ICU), providing emotional support, surrogate decision-making, and patient advocacy. 3 Visiting restrictions have kept families and patients apart, causing additional trauma to many.…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not observe similar results as Zeh et al with respect to discharge planning, we advocate for the necessity of novel ways to involve family members and friends (who may also play active roles as caregivers) in care decisions during times of physical hospital restrictions. As an example, the feasibility of a family centered, virtual visiting strategy in the ICU was recently highlighted by Thomas et al This strategy was successful in satisfying five essential criteria that virtual visiting needed to (1) simulate open and flexible visiting; (2) be able to accommodate differences in family size, dynamics, and cultural practices; (3) utilize a video conferencing platform that is private and secure; and (4) be easy to use and not require special teams to facilitate meetings; and (5) not increase the workload of ICU staff (21).…”
Section: Discussionmentioning
confidence: 99%
“…A teleconferencing initiative during the COVID-19 pandemic (Life Lines) that used simple, intuitive technology that functions independent of the hospital Wi-Fi, still encountered barriers, especially insufficient staff time to prepare virtual communication ( 32 ). Research is emerging on how best to implement video conferencing platforms into ICUs ( 36 ).…”
Section: Discussionmentioning
confidence: 99%